Cable‐Shaped Lithium–Sulfur Batteries Based on Nitrogen‐Doped Carbon/Carbon Nanotube Composite Yarns. Issue 8 (15th May 2019) - Yuan, Hongxin; Zhang, Miao; Yang, Chen; Liu, Lixuan; Lu, Ruichao; Mao, Lijuan; Wei, Zhixiang
Abstract: The research on flexible and wearable devices has attracted extensive attention in the last few years. Lithium–sulfur (Li‐S) batteries are regarded as a promising option because of their high theoretical capacity and energy density. Here, cable‐shaped Li‐S batteries are developed based on a nitrogen‐doped carbon/carbon nanotube/sulfur (NCNT/S) composite cathode and lithium metal anode. The carbon nanotube (CNT) yarns with high conductivity and an appropriate amount of doped nitrogen are synthesized by wet‐spinning followed by a carbonization process, and further act as a self‐supported conductive backbone for the active material. The NCNT/S yarns exhibit a high initial capacitance of 1001 mAh g −1 and excellent cyclic stability with 87% capacity retention after 200 cycles at 0.5 C. Furthermore, the assembled cable‐shaped Li‐S batteries by NCNT/S yarns present good ability to light up the LEDs for more than 8 h under normal and bending states at various angles, indicating that the cable‐shaped Li‐S batteries could be a prospective candidate for application in wearable electronics. Abstract : This work illustrates composite yarns based on the wet‐spinning method, and the yarn cathode for Li‐S batteries is achieved by a carbonization process. The flexible cable‐shaped Li‐S batteries are further successfully assembled and tested with NCNT/S‐700 yarn cathode and lithium foil anode, which are prospective for practical applications in wearable devices.